BITS-Tree -- An Efficient Data Structure for Segment Storage and Query Processing - Easwarakumar, K.S.; Hema, T. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper, a new and novel data structure is proposed to dynamically insert and delete segments. Unlike the standard segment trees, the proposed data structure permits insertion of a segment with interval range beyond the interval range of the existing tree, which is the interval between minimum and maximum values of the end points of all the segments. Moreover, the number of nodes in the proposed tree is lesser as compared to the dynamic version of the standard segment trees, and is able to answer both stabbing and range queries practically much faster compared to the standard segment trees.